THE PROBLEMATICS OF SPORTS LAW IN LATVIA: CIVIL AND CRIMINAL LAW STATUTORY ACTS PERSPECTIVE - Zalcmane, Karina; Kamenecka-Usova, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article shall be devoted to the problematics of Sports law in Latvia. Mainly authors shall be determining through the prism of civil and criminal law how does Sports law in Latvia looks like today, how it manifests itself and at what stage of development it allocates itself. The following chapters shall be observed:1) Introduction: the origin of Sports Law in Latvia, 2) Sports Law through the prism of civil law; 3) Sports Law through the prism of criminal law; 4) Conclusions. The main problematics in question is whether there exists sports law in Latvia and what are the controversial issues in the national legislation regarding sports. The article is based on the analysis of legislature and relevant documents.